2021
DOI: 10.1007/s10055-021-00570-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of display lag on vection and presence in the Oculus Rift HMD

Abstract: We used the Oculus Rift head-mounted display (consumer release -CV1) to simulate forward self-motion in depth. Observers made continuous yaw head movements at approximately 0.5 Hz or 1.0 Hz while viewing these selfmotion simulations. We examined the perceptual effects of increasing the head-to-display lag, by adding lag to the baseline lag of the system (estimated to be approximately 5.3 ms). We found that increasing the head-to-display lag up to 212 ms reduced the presence and the strength of the illusory sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Framerate refers to the rate at which the frame is changed in a video (which consists of a collection of still pictures), while latency or lag is the delay between the user input and the displayed output by the VR device (Lee et al 2020 ). A low framerate can cause flickering, which can lead to eye fatigue and headaches, whereas a large latency can increase visual-inertial sensory conflicts, leading to more intense levels of cybersickness (Lee et al 2020 ; Kim et al 2021 ; Palmisano et al 2017 ). On the other hand, vection is the ability of HMDs to generate illusions of self-motion by stimulating either the visual or non-visual senses (Kim et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Framerate refers to the rate at which the frame is changed in a video (which consists of a collection of still pictures), while latency or lag is the delay between the user input and the displayed output by the VR device (Lee et al 2020 ). A low framerate can cause flickering, which can lead to eye fatigue and headaches, whereas a large latency can increase visual-inertial sensory conflicts, leading to more intense levels of cybersickness (Lee et al 2020 ; Kim et al 2021 ; Palmisano et al 2017 ). On the other hand, vection is the ability of HMDs to generate illusions of self-motion by stimulating either the visual or non-visual senses (Kim et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A low framerate can cause flickering, which can lead to eye fatigue and headaches, whereas a large latency can increase visual-inertial sensory conflicts, leading to more intense levels of cybersickness (Lee et al 2020 ; Kim et al 2021 ; Palmisano et al 2017 ). On the other hand, vection is the ability of HMDs to generate illusions of self-motion by stimulating either the visual or non-visual senses (Kim et al 2021 ). Previous studies have found a positive relationship between vection and cybersickness, although the mechanisms for this relationship appear to be complex, with negative relationships emerging in some cases (Palmisano et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The poor latency in a VR system can lead to a time difference between expected and actual view, which can cause VR sickness [37]. The Oculus Rift CV1 HMD device (the device used in this study) has a very low baseline display delay of about 5.3 ms [38] and its motion to photon latency at the start (Sudden) and middle (Continuous) of the movement was 20.6 ms and 1.5 ms, respectively [39]. The results of comparing four conditions of time delay (67 ms, 167 ms, 267 ms and 367 ms) indicated that there was an increase in the severity of VR sickness with increasing time delay [40].…”
Section: Effect Of Visual Scenementioning
confidence: 99%
“…The results of comparing four conditions of time delay (67 ms, 167 ms, 267 ms and 367 ms) indicated that there was an increase in the severity of VR sickness with increasing time delay [40]. In addition, the increase in head-to-display delay up to 212 ms decreased the presence and vection in the Oculus Rift CV1 Headset [38]. Inconsistent findings showed no difference found in the severity of VR sickness between three conditions of time delay, including 48 ms, 125 ms and 250 ms [41].…”
Section: Effect Of Visual Scenementioning
confidence: 99%
“…When VIMS is experienced in VR, it is often referred to as Cybersickness (CS; Keshavarz et al 2015;Laessoe et al, 2023). Vection, however, appears to be a desirable sensation when using virtual reality (VR) applications as positive correlations have been found between vection and presence (e.g., Riecke et al, 2005a;Kim et al, 2022;. In return, the fidelity of VR applications could be enhanced through vection research (Hettinger et al, 2014).…”
Section: Introductionmentioning
confidence: 99%